Disain Simulator Automotive Air Conditioning Untuk Meningkatkan Kompetensi Mahasiswa - Kamin Sumardi; Wahid Munawar; Ridwan A.M. Noor (Jurnal Dinamika Pendidikan dan Pembelajaran, 2015)
The application of green technology in air conditioning technology, as it still uses refrigerants that contain chemical elements that damage the ozone layer and global warming. Over the field of air conditioning technologies that are environmentally friendly, yet coupled with the availability of labor in vocational and college levels are adequate, in both quantity and competence. This research aims to produce automotive air conditioning system simulator and learning models of air in the automotive sound environment-friendly technologies. Research using the method of research and development with the steps: a preliminary study, planning, development through simulator testing, validation, and final product. Simulator is made in accordance with the conditions in the workplace in order to avoid misconceptions and mala-practice automotive air conditioning system. This simulator is made compact and mobile or can be moved and carried. Learning model tailored to the needs of competence. The results showed that with the help of a simulator of automotive air conditioning and appropriate learning model students are able to grasp the concepts and practices 85% faster. Learning outcomes in the affective, cognitive, psychomotor and competence increased significantly.